HELLP syndrome complicated by pulmonary edema: a case report - Mai, Caiyuan; Wang, Bin; Chen, Rong; Duan, Dongmei; Lv, Lijuan; Lei, Qiong; Lin, Xiaohong; Wen, Jiying; Niu, Jianmin (Open medicine (Warsaw, Poland), 2018)
HELLP syndrome is a combination of symptoms described as hemolysis, elevated liver enzymes and low platelets. HELLP is a common life-threatening complication of pregnancy thought to be a variant or complication of preeclampsia. In this case report, we aimed to present a woman with acute postpartum HELLP syndrome complicated by pulmonary edema after caesarean section following severe preeclampsia. Our experience suggests that early detection of HELLP syndrome and timely management will bring good outcomes.